CO2 injection into saline carbonate aquifer formations II: Comparison of numerical simulations to experiments - B., Demiral (2008)

(untitled)
Sequestration of carbon dioxide in geological formations is an alternative way of managing extra carbon. Although there are a number of mathematical modeling studies related to this subject, experimental studies are limited and most studies focus on injection into sandstone reservoirs as opposed to carbonate ones. This study describes a fully coupled geochemical compositional equation-of-state compositional simulator (STARS) for the simulation of CO2 storage in saline aquifers. STARS models physical phenomena including (1) thermodynamics of sub- and supercritical CO2, and PVT properties of mixtures of CO2 with other fluids, including (saline) water; (2) fluid mechanics of single and multiphase flow when CO2 is injected into aquifers; (3) coupled hydrochemical effects due to interactions between CO2, reservoir fluids, and primary mineral assemblages; and (4) coupled hydromechanical effects, such as porosity and permeability change due to the aforementioned blocking of pores by carbonate particles and increased fluid pressures from CO2 injection. Matching computerized tomography monitored laboratory experiments showed the uses of the simulation model. In the simulations dissolution and deposition of calcite as well as adsorption of CO2 that showed the migration of CO2 and the dissociation of CO2 into HCO3 and its subsequent conversion into carbonate minerals were considered. It was observed that solubility and hydrodynamic storage of CO2 is larger compared to mineral trapping. © Springer Science+Business Media B.V. 2007.